PENDAMPINGAN MASYARAKAT DALAM UPAYA MENJAGA KESEHATAN LINGKUNGAN DI DESA BRABE KECAMATAN MARON KABUPATEN PROBOLINGGO - Putri Nurul Fatika; Pudji Rahmawati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
. Brabe Village, which is located in Maroon District, Probolinggo Regency, faces environmental problems that affect public health, including high stunting rates. The aim of this research is to identify the main problems related to environmental management, especially waste and sanitation, and propose solutions through educational programs and